Screening Saves Lives campaign: KAP assessment - Hallett, Jonathan; Leavy, Justine; Phoo, Nang; Crawford, Gemma; Khandu, Lekey (Collaboration for Evidence, Research and Impact in Public Health (CERIPH), 2023)
Cancer is a significant health concern for LGBTIQASB+ Australians, with an estimated 7,500 new diagnoses and 23,000 survivors annually. The WA Cancer Plan 2020-25 aims to reduce cancer’s burden and acknowledges the unique needs of those in the LGBTIQASB+ community. Ongoing disparities in cancer care experienced by LGBTIQASB+ individuals lead to exclusion, lack of support, and increased distress. Discrimination in healthcare settings and a lack of LGBTIQASB+ competence among clinicians hinder cancer screening uptake, especially among trans people. There is a notable absence of LGBTIQASB+-specific information in Australian cancer support resources, with recent initiatives beginning to address this gap. Launched in 2021, the Screening Saves Lives campaign targets the WA LGBTIQASB+ community, promoting awareness and engagement in bowel, breast, and cervical cancer screenings. WA LGBTIQASB+ community members were featured in campaign resources, with widespread dissemination through various LGBTIQASB+ community channels and through healthcare providers. This study aimed to evaluate the campaign and assess cancer screening knowledge, attitudes and practices in the WA LGBTIQASB+ community.